Optimal Design of Multi-Span Pitched Roof Frames with Tapered Members - Kaveh, Ali; Kabir, Mohammad Zaman; Bohlool, Mahdi (Periodica Polytechnica Civil Engineering, 2019)
Many industrial buildings require large spans and high height, and the use of a frame with inclined roofs with non-prismatic elements can reduce the usage of steel. Pitched roof frame with single spans are optimized using different meta-heuristic algorithms. In this paper, the optimal design of industrial frames with two and three spans under gravity and lateral loads is performed. Five efficient and widely accepted optimization algorithms are used to optimize each frame. The convergence histories and design results of these algorithms are compared and the most suitable algorithm is determined. In each frame, the effect of increasing the apex height is evaluated on the optimal weight and the best angle is determined for optimum weight.